2005
DOI: 10.1037/0021-843x.114.2.259
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Disorder Symptomatology Among Partners of Men in Treatment for Relationship Abuse.

Abstract: This longitudinal study examined posttraumatic stress disorder (PTSD) symptoms among current and former female partners (N = 96) of men participating in a group treatment program for partner abuse perpetrators. Female partner probable PTSD rates, obtained during time points corresponding with pretreatment, posttreatment, and 6-month follow-up for the male clients, were 52%, 34%, and 29%, respectively. Psychological abuse exposure was more strongly and uniquely associated with PTSD symptoms than was physical ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
53
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(66 citation statements)
references
References 51 publications
10
53
1
2
Order By: Relevance
“…Further, the results of this study come to underline that physical damage most often accompanies the attitude of disrespect and humiliation, experiences that are very damaging to the psychophysical health (28). Our findings are in line with the results of studies that report that "complex violence" appears with high frequency in the cases of violence against women who file in court (24,15).…”
Section: Discussionsupporting
confidence: 82%
“…Further, the results of this study come to underline that physical damage most often accompanies the attitude of disrespect and humiliation, experiences that are very damaging to the psychophysical health (28). Our findings are in line with the results of studies that report that "complex violence" appears with high frequency in the cases of violence against women who file in court (24,15).…”
Section: Discussionsupporting
confidence: 82%
“…Consistent with one previous study (Mitchell & Hodson, 1983), relationship abuse frequency was more strongly associated with disengagement coping than engagement coping. Higher levels of each form of abuse were associated with disengagement coping behaviors, and psychological aggression was the strongest unique predictor of disengagement coping A growing literature shows psychological aggression to be a particularly robust predictor of PTSD symptoms among battered women (Arias & Pape, 1999;Dutton et al, 1999;Taft, Murphy, King, DeDeyn, & Musser, 2005). The stronger relationship between psychological aggression and disengagement coping in this study may reflect the particularly damaging effects of this form of abuse on mental health.…”
Section: Discussionmentioning
confidence: 52%
“…A study by Follingstad, Rutledge, Berg, Hause, and Polek (1990) found that 72% of female victims of PA reported that they believed that their experiences of psychological abuse had a greater effect on their mental health than their experiences of physical abuse. In fact, there has been some support for the idea that psychological abuse might be a better predictor of mental disorders than physical abuse (Dutton, Goodman, & Bennett, 1999;Taft, Murphy, King, Dedeyn, & Musser, 2005). Arias and Pape (1999) found in a study of 68 women residing in a battered women shelter that although physical abuse severity and frequency did not significantly predict PTSD, psychological abuse was a significant predictor of PTSD even after controlling for physical violence.…”
mentioning
confidence: 92%